The fertile desert : a history of the middle Euphrates Valley until the arrival of Alexander - Al Khabour, Anas, (Archaeopress Archaeology, 2022)
Reconstructs the history of the Euphrates Valley between the mouths of the Balikh and the Khabour. Several surveys, archaeological expeditions, and interventions of the Syrian Directorate of Antiquities, have made a significant amount of data available which contribute to an improved overview of the region.